(untitled) (Biological Sciences - PJSIR, 1997)
organic monobasic acids of compositions, trans-j’I’i (U)2 U ’1 Cl and K[VOUL’ ’1 S04 (LI =dcprotonatecl acetic acid, propionic acid, butyric acid and benzoic acid and L" = trans-[14J-diene) have been isolated and characterized by elemental analyses, conductivity anclmagnetic measurements, IR and electronic spectral studies, Titanium (III) corn- plexes exhibit 3:I and oxovanadium (IV) complexes show 2: I electrolytic behaviour in DMSO as arc evident from conductivity measurements. Magnetic measurements, IR and electronic spectral data reveal octahedral stereochemis- try for both titanium (III) and oxovanadium (IV) complexes.